PENGARUH UKURAN PERUSAHAAN, KEPEMILIKAN INSTITUSIONAL, PROFITABILITAS TERHADAP INTEGRATED REPORTING DENGAN AUDITOR EKSTERNAL SEBAGAI VARIABEL MODERASI (STUDI PADA PERUSAHAAN MANUFAKTUR DI BEI TAHUN 2014-2018) - liana, sherry; JMV Mulyadi; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2020)
This study aims to examine and analyze the effect of company size, institutional ownership and profitability on Integrated Reporting with external auditors as a moderating variable. The sample used was a real estate sector manufacturing company listed on the Indonesia Stock Exchange in 2014-2018. The research method used is a quantitative method and is processed using the Eveiews application 10. The results show that company size and institutional ownership have a significant effect on Integrated Reporting, while profitability variables have no significant effect on Integrated Reporting. The results of company size variables that are moderated by external auditors have a significant effect on Integrated Reporting, while institutional ownership variables and profitability that are moderated by external auditors have no significant effect.